PROBLEM SOLVING SUDOKU MENGGUNAKAN ALGORITMA GENETIKA - Jimmy Hadinata (SISFOTENIKA, 2011)
Abstracts: Sudoku is a logical puzzle that using numbers as the symbol to play, it has a quite interesting problem to be solved, Genetic Algorithm is suited as a problem solving for sudoku because Genetic algorithm method is to find solution with an optimization when Sudoku need an optimization to find the solution. Designing Sudoku with Genetic Algorithm as the problem solver could solve sudoku faster because Genetic Algorithm always produce a new better solution every loop that called Generations with selection, crossover and mutation process to create a new solution.Keywords: Sudoku, Genetic Algorithm, Problem Solving, Generations, Selection, Crossover, Mutation